Building Communication and Collaboration Skills through Inter-professional Simulation Design Challenges - Amelia Huelskamp; Chase DuBois (Academic Chairpersons Conference Proceedings, 2023)
This presentation focuses on the benefits of inter-professional education, provides an overview of a sample project, and offers recommendations for inter-professional collaboration in higher education.
Keywords: inter-professional; inter-disciplinary; cross-curricular; collaborative; simulation